1996
DOI: 10.1161/01.str.27.5.847
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke in a Cohort of 815 Patients With Calcification of the Aortic Valve With or Without Stenosis

Abstract: Aortic valve calcification with or without stenosis is not a risk factor for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Valve calcifications and stroke were examined in two large cohorts; it was concluded that mitral [5]but not aortic [6]valve calcification is a risk factor for stroke. In spite of these findings, we found 5 published cases of documented cerebral SCE from the aortic valve [1, 7, 8, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Valve calcifications and stroke were examined in two large cohorts; it was concluded that mitral [5]but not aortic [6]valve calcification is a risk factor for stroke. In spite of these findings, we found 5 published cases of documented cerebral SCE from the aortic valve [1, 7, 8, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…6 We hypothesized that calcific AS is associated with the same pathobiology underlying an increase in the CHA 2 DS 2 -VASc score and that the latter, therefore, could be particularly useful for stratifying risk of stroke in earlier stages of AS. This study was, therefore, undertaken to examine the ability of the CHA 2 DS 2 -VASc score to predict ischemic stroke in asymptomatic patients with AS with and without coexisting AF.…”
mentioning
confidence: 99%
“…4,5 Several, 6,7 although not all, 8,9 studies have detailed a similar relationship between MAC and stroke, but an independent association between AV calcification and cerebral infarction has only been demonstrated in the presence of AV stenosis. 5,10,11 MAC and AV sclerosis are associated with atherosclerosis risk factors that can promote left ventricular (LV) hypertrophy and left atrial (LA) enlargement, each of which has been reported to predict cerebrovascular events. 12,13 However, available studies linking valvular calcification with cerebral ischemia have adjusted only partly, if at all, for these concurrent echocardiographic predictors.…”
mentioning
confidence: 99%